Kontribusi Gaya Belajar Dan Kemampuan Kognitif Mahasiswa Teknik Elektronika Terhadap Hasil Belajar Mahasiswa Pada Mata Kuliah Teknik Digital di Jurusan Teknik Elektronika Fakultas Teknik Universitas Negeri Padang - Ainil Witri; Yusri Abdul Hamid; Khairi Budayawan (Voteteknika (Vocational Teknik Elektronika dan Informatika), 2014)
The background of this research has by problem  learning outcomes in digital technique subject was low then student in electronics technique majors of FT UNP, where 93,68% student which not yet reached value ≥ B. This research is purposed to reveal the contribution style learn and cognitive ability to learning outcomes in subject of digital technique in electronics technique majors of FT UNP. This research type is descriptive which have the character of correlation.The population of this research was totaled of95 people and sampel 49 people student study program education electronics technique of semester january-june 2013. Using technique of random sampling (Simple Random Sampling). Data learning outcomes student obtained in subject of digital technique in electronics technique majors of FT UNP. While data style learn and collected cognitive ability to enquette by using scale of likert which have been tested validity and reliability. data were analyzed use statistical methods constructively Microsoft Excel software 2007.The result of data analysis showed: (1). style learn to give contribution equal 18,38% to  student learning outcomes in Majors Technique Electronics of FT UNP (2). cognitive ability give contribution equal  22,56% to studentlearning outcomesin Majors Technique Electronics of FT UNP (3). style learn and cognitive ability by together give contribution equal 25,61% to student learning outcomesin Majors Technique Electronics . Become can be concluded that style learn and cognitiveability  have contribution to learning outcomes, progressively style goodness learn student in course of learning to teach andcognitive ability excelsior of student, hence result learn of excelsior.Keywords: Style Learn, cognitive ability, Learning Outcomes,                Descriptive Correlational, Simple Random Sampling.